2020
DOI: 10.26452/ijrps.v11i3.2779
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low back pain on fear of movement and functional activities

Abstract: Fear is an uncomfortable feeling, which results from the proximity of actual threat or pain. A strong correlation exists between fear and pain. Kinesiophobia is the phobia of activity and physical movement, which results from a sensation of sensitivity to painful injury or reinjury. Low back pain (LBP) is among the frequent disorders of the musculoskeletal system. LBP is mainly due to bad postures and poor organisational ergonomics. Kinesiophobia has adverse effects on rehabilitation outcomes. So the systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This is supported by the observation that for patients that exhibited a significant change in these variables when responding to the questionnaire conducted by the physicians (see Supplementary Materials S5), their answers showed that most of them were better when performing activities that involved a high degree of movement from their point of view, such as going up the stairs or walking. Furthermore, as the velocities of the patients also seemed to have improved, this could be related to the therapies helping patients to overcome their fear of movement so that they were less hesitant to move, therefore decreasing the overall time it took them to perform an activity [41,42]. Overcoming the fear of movement would correlate with the improvement in these variables with overall improvement in performing daily activities.…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by the observation that for patients that exhibited a significant change in these variables when responding to the questionnaire conducted by the physicians (see Supplementary Materials S5), their answers showed that most of them were better when performing activities that involved a high degree of movement from their point of view, such as going up the stairs or walking. Furthermore, as the velocities of the patients also seemed to have improved, this could be related to the therapies helping patients to overcome their fear of movement so that they were less hesitant to move, therefore decreasing the overall time it took them to perform an activity [41,42]. Overcoming the fear of movement would correlate with the improvement in these variables with overall improvement in performing daily activities.…”
Section: Discussionmentioning
confidence: 95%
“…LBP is mostly caused by poor posture and organizational ergonomics. LBP is often dealt with conservatively Physiotherapy, in the form of physical exercises, is important in treating patients 7 .…”
Section: Introduction Introductionmentioning
confidence: 99%